Analysis on the Teaching Path of Youth Volunteer Service Integrated into Ideological and Political Courses in Colleges and Universities - Wang, Zhanhang (Transactions on Social Science, Education and Humanities Research, 2024)
The Internet, big data and the Internet of Things are developing like bamboo shoots after a spring rain. Volunteer service on the express train has become an important way for contemporary youth to participate in social practice and improve their quality. As the core course of ideological and political education for college students, ideological and political courses in colleges and universities, how to effectively integrate the elements of youth volunteer service, and improve the effectiveness and pertinence of ideological and political courses, has become an important topic facing ideological and political education in colleges and universities. This paper starts with the necessity of integrating youth volunteer service into the teaching of ideological and political courses in colleges and universities, analyzes the opportunities and challenges of integrating youth volunteer service into ideological and political courses, so as to put forward the path of "one body and two arms" to help improve the effectiveness and appeal of ideological and political courses in colleges and universities.